CIVIL SOCIETY DI INDONESIA: SUATU KONSEKUENSI LOGIS TERWUJUDNYA GOOD GOVERNANCE - Adriani Adnani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Civil society is one of the three important sectors of society, along with government and business. Civil society is one of the important elements of the democratization process in Indonesia. In accordance with the problems formulated above, the purposes of this discussion are to find out the description of civil society in Indonesia, and to find out efforts to strengthen civil society as a logical consequence of the realization of Good Governance in Indonesia. The development of civil society involves all aspects and dimensions of life. Therefore, efforts and commitment are needed to strengthen the community. Cooperation is needed because no party, organization, institution or anything even the government can carry it out alone. The relationship between civil society and good governance is symmetrical between the two. This is because the two concepts were born from the concept of democracy that upholds the values of justice, freedom, individual and group rights. Furthermore, democracy requires the state in carrying out its activities to be open to the public. Strengthening civil society in the flow of democracy must be realized as an absolute necessity for the implementation of a 'strong' and 'clean' government. The weakness of civil society in Indonesia is marked by widespread rejections of state/government policies by the people and these rejections have not received a meaningful response from the state/government. In the process of determining policies, the government bureaucracy still feels that citizens are used as objects of policy. This kind of narrow view will make the government anti-suggestions from citizens in determining policies.